Tokenization of creativity: user motivation, consensual value and Chinese copyright law - R. A. Budnik (Правоприменение)
The subject of this study is the legal-economic analysis of the non-fungible token phenomenon. Due to the a priori accessibility of many tokenized intellectual products, the ability to monetize them by copyright methods turns out to be hard to implement. The paper puts forward a hypothesis that token owners apply innovative monetization methods, which do not stand on the prohibition and restriction of access to the protected results of intellectual activity. Instead of deactivated copyright restrictions, token buyers receive some new, additional, non-trivial economic utility that researchers have not reflected yet. If this utility exists, we should identify, analyze and include it in the equation of relations regarding NFT. The second hypothesis of the study stems from the first one. It states that the results of creative activity in the post-economic society take the place of a new etalon of value, which replaces the materialistic standard of worth based on rarity. The consensual value contained in tokenized works brings additional motivators for token purchasers and compensates for the lost sources of income.Our goal is to put and verify the scientific hypotheses of tokenized works' additional non-obvious value existence. We suppose that this innovative utility substitutes traditional copyright ban-based monetization abilities. The research's purpose is also to theoretically generalize its results and formulate a legal-economic concept that explains the motivation for the purchasers of non-fungible tokens and sets the regulations for the NFT market.Methodology. The study of the non-fungible token phenomenon and the verification of formulated hypotheses conducts from the standpoint of the law, economics, an interdisci-plinary legal-economic – institutional point of view, as well as with the help of the monistic copyright doctrine of the People's Republic of China. The research methodology also includes an analysis of the relevant body of knowledge and various points of view of the scientists on the subject of research.The study's main result is the novel elaborated concept of the non-fungible token owner's moral right. This concept fills the rising doctrine of utilitarian digital rights with legal-economic essence. We constructed the non-fungible token owner's moral right consisting of two powers: the right to designate one's name as the owner of a token for a specific creative product and to demand such an indication from others; and also, as a duty of NFT platforms to support the function of informing about the name or pseudonym of the token's owner.Analysis of the appropriate accumulated knowledge, development, and verification of formulated hypotheses on tokenized works' consensual value and additional economic utility, allowed us to achieve the goals of this study. We resolve the issue of token purchasers' motivation and legal-economic grounds for their rational behavior by formulating and substantiating the concept of non-fungible tokens' owner moral right.